XANTHONES FROM THE TWIGS OF THE VIETNAMESE CALOPHYLLUM CERIFERUM GAGNEP. EX STEVENS - Thi Minh Hang, Nguyen; Van Hung, Nguyen; Quyet Chien, Nguyen (Vietnam Journal of Science and Technology, 2017)
Three xanthones have been  isolated  from  the dichloromethane extract of  the  twigs of  the Vietnamese  Calophyllum  ceriferum  Gagnep.  Ex  Stevens  collected  at  Ninh  Thuan  province. Their  structures  were  elucidated  as  1,7-dihydroxy-2,3,8-trimethoxyxanthone,  1,7-dihydroxyxanthone and 1,6-dihydroxy-5,7-dimethoxyxanthone by spectroscopic analyses.